2018
DOI: 10.26525/jtfs2018.30.4.537545
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterisation of an Anthropised Atlantic Forest Fragment

Abstract: The present study aimed to evaluate the functional expression of tree sinusiae in three sectors of a forest fragment in relation to different land use histories. The study recorded the number of individuals, number of individuals with multiple stems and number of tillers, calculated the percentages of tillered individuals and species, and then classified the species into regeneration and dispersal guilds. The most anthropised sector of the forest showed higher tillering and a larger proportion of pioneer and l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 10 publications
0
1
0
1
Order By: Relevance
“…Fire interval is an important factor for savannic areas because it determines processes such as sowing, germination, fruiting and flowering [18]. Thus, it is concluded here that the vegetation in Area 1 is still in the process of regeneration and Area 2 is stabilized, suggesting a community formed by species of rapid regeneration and therefore resistant to fire.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…Fire interval is an important factor for savannic areas because it determines processes such as sowing, germination, fruiting and flowering [18]. Thus, it is concluded here that the vegetation in Area 1 is still in the process of regeneration and Area 2 is stabilized, suggesting a community formed by species of rapid regeneration and therefore resistant to fire.…”
Section: Discussionmentioning
confidence: 64%
“…Phytosociological analysis comprised two fundamental stages. The analytical stage integrates sample design, collection of plant material and identification of species, while the synthetic stage culminates with the comparison of data among sample units for classification [18]. It is in this stage that the identification and classification of floristics was carried out in the four study areas.…”
Section: Floristic Composition and Structure Of The Plant Communitymentioning
confidence: 99%
“…Campomanesia xanthocarpa was less abundant in both areas, but the aggregate distribution in Logged Forest was also due to the higher density of individuals in the smaller size classes. A higher degree of aggregation in smaller individuals is common for tropical tree species (Condit et al, 2000;Fonseca et al, 2004;Morel et al, 2018). Condit et al, (2000) found that the aggregation of juveniles suggests habitat-related patchiness or dispersal limitation.…”
Section: Resultsmentioning
confidence: 99%
“…Para verificar a composição das guildas de regeneração das populações de cada setor (borda e interior), as espécies foram classificadas em: pioneiras (P), cujos indivíduos necessitam de luz direta para germinar e se estabelecer, clímax exigente de luz (CEL), que precisam de luz quando jovens para atingir o dossel, e clímax tolerante à sombra (CTS), que são as espécies cujas sementes germinam e crescem sob a sombra, em condições de sub-bosque. Essa classificação foi feita a partir da metodologia usada por Morel et al (2018).…”
Section: Methodsunclassified